KONSTRUKSI PAI BERBASIS ADAB UNTUK MEMPERKUAT IDENTITAS SISWA DI ERA DISRUPSI - Abu Bakar Dja'far; Andi Hidayat (STKIP Pesisir Selatan, 2026)
The current era of technological disruption brings radical challenges to the existence of Islamic education, where the flow of digital information often blurs the boundaries of ethics and students' identities. This study aims to analyze the strategy of constructing Islamic Religious Education (PAI) based on adab (ethics) as an effort to strengthen student identity in Madrasah Ibtidaiyah (Islamic elementary schools) in facing the dynamics of this disruptive era. Through a qualitative method with a case study approach, data were collected using in-depth interviews, participatory observation of daily religious practices, and curriculum documentation studies. The results show that teachers' efforts in constructing adab begin with instructional planning that explicitly integrates the values ​​of tabayyun (religious trust), amanah (trustworthiness), and tawadhu (religious humility) into teaching materials and digital interactions. Teachers play a central role as motivators through role models (uswah hasanah) that foster students' intrinsic pride in their Muslim identity, and as evaluators through authentic assessments that monitor the consistency of student behavior. Although the construction of adab has proven effective in building moral immunity, its success still faces obstacles in the form of dual student identities in the digital space and a lack of value synergy with the family environment. The conclusion of this study confirms that strengthening Islamic identity in the era of disruption requires an integrated